Interpersonal Competences and Attitude to Online Collaborative Learning (OCL) among Future Pedagogues and Educators-A Polish and Portuguese Perspective - Monika Frania; Fernando Luís de Sousa Correia (MDPI AG, 2022)
Interpersonal competences in relationship building, collaboration and teamwork are essential both in F2F education and in distance or hybrid styles of education. In the face of the COVID-19 crisis, as well as previous trends, some or all of the higher education didactics were transferred to the online environment. In this context, the Online Collaborative Learning (OCL) model, now known as collaborativism, is gaining importance. This research aims to diagnose and compare the level of interpersonal competences and attitude in the OCL model among students preparing for the profession of an educator, pedagogue or teacher in the autonomous region of Madeira and in Poland. Quantitative studies were conducted using the Interpersonal Competence Questionnaire by D. Buhrmester, W. Furman, M.T. Wittenberg and H.T. Reis-as adapted by Poland and Portugal. In addition, the respondents expressed their views on OCL in the self-written questionnaire. According to the research findings, the highest level of competence in the Portuguese group was achieved by the respondents in terms of: Emotional Support (EW), Conflict Management and Resolution (RK) and Negative Assertion-Asserting Influence (AO). In the Polish group, EW was the lowest. The highest level of interpersonal competences was observed for Conflict Management and Resolution (RK), Disclosure (US) and Initiation (IR). The largest group of the surveyed students in both countries expressed a positive attitude towards implementing OCL in their courses of study and declared their willingness to be a member of a group that learns online together.